REPRESENTATION OF MARRIED YOUNG WOMEN IN “A DAY IN MY LIFE”: AFFIRMATION AND NEGOTIATION OF THE CONSTRUCTION OF FEMININITY IN TIKTOK - Wemmy Sihombing; Shuri Mariasih Gietty Tambunan (Fakultas Komunikasi, Sastra, dan Bahasa, 2023)
A Day in My Life (ADML) videos are TikTok contents that describe what the TikTokers do in their everyday lives. This research aims to explore how femininity is constructed through ADML videos. By utilizing textual analysis methods, this article highlights how Indonesian female TikTokers affirm or negotiate with the dominant ideology in the society, in this case patriarchal ideology. Research findings reveal that in their content, @sindisafitrii and @gelialinda affirm the patriarchal ideology by constructing the notion of marrying at such a young age due to social factors and culture constructions. Furthermore, they also construct the idea of marriage as “halal” or lawful or permitted under Islamic law. On the other hand, ADML videos by both TikTokers are also ambiguous in portraying the domestic role divisions between husband and wife. On one side, husbands are portrayed to have a balanced gender role with their wives. However, in some videos, the narratives showcase how uncommon it is for husbands to be involved in domestic roles and how they are glorified for doing their chores in the domestic area. Research findings also uncover that these ADML videos portray how women should gain personal financial security; even though they also depict that the reason why the two TikTokers choose to get married at a young age is for financial security. The ambiguous portrayal of how femininity is constructed in both TikTok accounts through their A Day in My Life videos represents how they affirm yet negotiate with patriarchal ideology.